Modeling individual differences in automatic evaluation measured by Evaluative Decision Task - Rebernjak, Blaž (Array, 2013)
The study deals with the measurement of individual differences in automatic processing of affective stimuli within affective priming paradigm. Automatic processing measures, termed processing tendencies, were defined by parcels composed of difference score items of the Evaluative Decision Task reaction time variables. Confirmatory factor analytic framework was used to (1) construct parcels of individual items and evaluate them in terms of unidimensionality and temporal invariance, (2) examine the structure of relationships among the processing tendencies ; and (3) test the stability of individual differences in processing tendencies in a four week period. Random assignment of items to parcels showed unidimensionality as well as invariance over time. Processing tendencies relating to same-valence targets–facilitation and inhibition of positive targets as well as facilitation and inhibition of negative targets–showed a positive relationship in both time points not predicted by theory. Furthermore, evidence in favor of stability of individual differences in processing tendencies was obtained for positive targets, while the results for negative targets were less clear. The results are interpreted in light of current theories of automatic affective processing.